Lipid-based floating multiparticulate delivery system for bioavailability enhancement of berberine hydrochloride - Rakesh Mishra, Shashikant Dhole (Journal of Applied Pharmaceutical Science, 2019)
The objective of the present investigation was to design and optimize lipid-based floating multiparticulate of Berberine hydrochloride (BERH), so as to increase its solubility and to reduce P-Glycoprotein mediated efflux in the intestine, hence to improve oral bioavailability. Solid dispersions were prepared using hydrophilic carriers gelucire 44/14 and gelucire 50/13 in different ratio. The prepared solid dispersion of BERH was further formulated into sustain release gastroretentive floating pellets using hydrophobic lipid carrier gelucire 43/01 as release retardant, sodium bicarbonate (NaHCO3 ) and hydroxylpropyl methyl cellulose K4M (HPMC K4M) as gas former and matrix polymer, respectively. The effect of amount of gelucire 43/01 and NaHCO3 : HPMC K4M were studied and optimized using a 3-level, 2-factor, factorial design. Solid dispersion of BERH compared to pure drug showed 4-fold enhancement in aqueous solubility. The optimum system could float for more than 8 hours and showed 88.46% drug release in 8 hours. The pharmacokinetic study conducted in male Wistar rats indicated 2.32-fold increase in relative bioavailability of optimized formulation compare to the marketed tablet. The lipid-based floating pellets of BERH were obtained and could be an applicable choice to deliver BERH with improved bioavailability in effective use for various clinical applications.
Keywords: Berberine hydrochloride, gelucire, solid dispersion, lipid floating multiparticulate, gastroretentive.